Establishing reference values for amplitude-integrated electroencephalography in preterms below 35 weeks of gestational age: A prospective observational cohort study - Han, Young Mi; Lee, Na Rae; Bae, Mi Hye; Park, Kyung Hee; Lee, Yun Jin; Nam, Sang Ook; Byun, Shin Yun (The Turkish Journal of Pediatrics, 2016)
Characteristic patterns in amplitude-integrated electroencephalography (aEEG) develop with gestational age (GA), and so can be used to evaluate brain maturation in premature infants. Reference aEEG values in normal preterm infants have not been identified and data are scarce. We aimed to validate a currently available aEEG scoring system. We also investigated the development of aEEG activity during the first week after birth, determining reference values in preterm infants with no abnormal cranial ultrasound findings. We prospectively studied aEEG and cranial ultrasounds in infants with a GA of < 35 weeks. We conducted aEEG at 12-14 hours, 46-48 hours, 70-72 hours, and 1 week after birth. The aEEG recordings were evaluated using Burdjalov criteria, scored by two independent neonatologists. Thirty-four infants were enrolled and completed the 1-week evaluation. GA ranged from 24 to 35 weeks and birth weights varied between 570 and 2,100 g. We analyzed 134 aEEG tracings, with a mean difference between raters of -0.05. Total scores, summed from scores for each assessed variable, increased gradually with advancing gestational and postnatal age. However, highest scores were not attained until 35 weeks' gestational age. There was high inter-rater agreement for aEEG scoring, and we could ascertain some approximate reference values for aEEG development in preterm infants at varying GA. To establish standardized aEEG reference criteria, further studies in larger cohorts of premature infants should be performed over longer periods.
Keywords: amplitude-integrated electroencephalography; cerebral function monitor; preterm infant; reference values